Analisis Seismisitas dan Percepatan Tanah Maksimum untuk Evaluasi Risiko Gempabumi di Pulau Bali Periode Tahun 1980 - 2023 - Adelia Wahyu Anjani; Winardi Tjahyo Baskoro; I Putu Dedy Pratama; I Nengah Artawan; Ni Luh Putu Trisnawati; I Wayan Supardi (Universitas Hamzanwadi, 2026)
Bali Island is located in an active tectonic zone due to the meeting of the Indo-Australian and Eurasian Plates, thus experiencing significant seismic activity. This study aims to analyze the seismicity characteristics, distribution, and magnitude of peak ground acceleration (PGA), and evaluate earthquake risk in Bali Island. Earthquake data for the period 1980–2023 were analyzed based on spatial and temporal distributions and the Gutenberg-Richter equation to assess the relationship between earthquake frequency and magnitude. The analysis results show that Bali's seismicity is dominated by shallow earthquakes (<60 km) with moderate magnitudes (4.5 ≤ M < 6.0) to large magnitudes (M ≥ 6.0). The highest earthquake density is in the Central and Eastern regions of Bali with an earthquake density reaching 0.02 events/km². PGA values ​​range from low to exceed 0.4 g, especially in the Central and Southeast regions associated with active faults and the Southern subduction zone. These findings provide an important basis for spatial planning, earthquake-resistant building structure design, and earthquake risk mitigation strategies on the island of Bali.